PEMANFAATAN KULIT PISANG SEBAGAI MEDIA PENYERAPAN LOGAM PADA LIMBAH CAIR (REVIEW JURNAL) - Dian Yanuarita; Anggita Sutra Pratiwi; Shania Miranda Rossa Saragih (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2020)
This thesis, the main ingredient is banana peel as an adsorbent to absorb cadmiun metals. The purpose of this thesis is relationship activator use in adsorbents, the relationship between contact time with percent removal, and the relationship between adsorbent mass and percent removal. Making activated carbon, banana peels must be carbonized using temperatures around 300-500-5C, while making biosorbents without the carbonization process. The best activator on activated carbon is HCl, whereas the biosorbent is NaOH. Optimal contact time in using cadmium using activated carbon for 90 minutes with 98.35% removal, while using biosorbent for 3 minutes with 99% removal. And the optimal adsorbent mass of cadmium uses activated carbon of 0.8 gr with 98% removal, while the biosorbent mass of 15 gr with 99.21% percent removal. It can be concluded that the use of biosorbents as an insertion media is more effective in metal deviations compared to using activated carbon.